ChemInform Abstract: Synthesis of Diazirine‐Based Photoreactive Saccharin Derivatives for the Photoaffinity Labeling of Gustatory Receptors. Issue 37 (September 2015) - Hashimoto, Makoto; et al.
Abstract An improved short synthesis of diazirinyl saccharin derivatives (VIII) and (X) is presented.